EVAAN: An empirical verification argument against naturalism - Blondé, Ward (Logos. Anales del Seminario de Metafísica, 2023)
Alvin Plantinga’s evolutionary argument against naturalism (EAAN) claims that if both naturalism (N) and evolutionary theory (E) are true, then all our beliefs are unreliable (premiss 1). Consequently, given N&E, the belief in N&E is unreliable (premiss 2) and N&E is self-defeating (conclusion). My empirical verification argument against naturalism (EVAAN) is more cautious and improves Plantinga’s EAAN by withstanding a rejoinder of the evolutionary naturalist to premiss 1. EVAAN claims that metaphysical beliefs are unreliable, given N&E (premiss 1a). This anticipates the evolutionary naturalist’s claim that empirical verification plays a crucial role in peer assessments and sexual selection of intelligence, and that, therefore, N&E makes empirically verifiable beliefs often reliable (premiss-1 rejoinder). However, even then it can be argued that the belief in N&E is unreliable, given N&E (premiss 2), because N&E is metaphysical (premiss 1b) and therefore not empirically verifiable. My EVAAN distinguishes reliably verifiable intelligence from metaphysical intelligence and claims that, if N&E is true, humans are lacking metaphysical intelligence. This paper also contains an argument against Plantinga’s EAAN, by supporting the premiss-1 rejoinder.
Keywords: Evolutionary argument against naturalism; Alvin Plantinga; Evolutionary reliability; Evolution by natural selection; Epistemology; Supernaturalism; Intelligence; Just-so stories